Response Site Analyses of 3D Homogeneous Soil Models - Davide Forcellini; Marco Tanganelli; Stefania Viti (Emerging Science Journal, 2018)
The seismic excitation at the surface can be determined through Site Response Analyses (SRA) as to account for the specific soil properties of the site. However, the obtained results are largely affected by the model choice and setting, and by the depth of the considered soil layer. This paper proposes a refined 3D analytical approach, by the application of OPENSEES platform. A preliminary analysis has been performed to check the model adequacy as regards the mesh geometry and the boundary conditions. After the model setting, a SRA has been performed on various soil profiles, differing for the shear velocity and representing the different soil classes as proposed by the Eurocode 8 (EC8). Three levels of seismic hazard have been considered. The seismic input at the bedrock has been represented consequently, through as much ensembles of seven ground motions each, spectrum-compatible to the elastic spectra provided by EC8 for the soil-type A (bedrock). Special attention has been paid to the role of the considered soil depth on the evaluation of the surface seismic input. Different values of depth have been considered for each soil type and seismic intensity, in order to check its effect on the obtained results.